Investigating the biophysical, biochemical, and biological activity of anti-cancer zinc oxide nanoparticle and its physiometacomposite (PMC) nanoparticles - Mathew, Elza Neelima (Kansas State University, 2020)
Combating melanoma, the most lethal form of skin cancer, our research group works towards assessing the anticancer potential of zinc oxide (ZnO) nanoparticle and its different physiological metal oxide nanoparticles or physiometacomposite (PMC) nanoparticles. Among these, the antimelanoma cytotoxic activity of zinc oxide nanoparticle (ZnO NP; 100 nm) has been extensively demonstrated. The objective of the proposed study is to elucidate the biophysical, biochemical, and biological mechanisms of the anti-cancer activity of ZnO NP and its PMCs. For biophysical and biochemical characterization, dynamic light scattering (DLS), two-dimensional fluorescence difference spectroscopy (2-D FDS), transmission electron microscopy (TEM) and inductively coupled plasma mass spectrometry (ICP-MS) have been used. The biological activity of the different nanoparticles was investigated in NIH3T3 mouse fibroblast cells and B16F10 mouse melanoma cells followed by in vivo investigation in a mouse model. The behavior of the nanoparticles in different mouse tissues was also monitored ex vivo. This dissertation presents the significant findings of this study. Chapter 1 gives a general introduction to the dissertation and an overview of ZnO NP, its anti-cancer activity, in vivo behavior, and a brief outline on melanoma particularly drug resistant and rarer forms. Chapter 2 is a detailed review of the anticancer activity of zinc oxide nanoparticles and combining ZnO NPs with nucleic acid therapeutic and protein delivery against metastatic melanoma. Chapter 3 investigates the immunological activity of zinc oxide nanoparticle and its anticancer peptide and RNA complexes. Chapter 4 characterizes the biochemical activities of ZnO NP and its PMCs in terms of inhibition of enzyme activities and associations of enzymes involved in the RAS pathway of metastatic progression. In Chapter 5, the interaction of ZnO NP with proteins using Ras binding Domain (RBD) as the model protein is investigated. In chapter 6, the combinatory anti-melanoma potential of ZnO NP and LL-37, an antimicrobial peptide, which is currently in clinical trials against melanoma is investigated. Chapter 7 summarizes the main findings from the previous chapters. An in-depth investigation of the cellular mechanisms and in vivo physiological/pathological effects is expected to help in molding new therapeutic targets and approaches. Demonstration of precise mechanisms of action is expected to help with the development of further therapeutic approaches utilizing ZnO NP.
Keywords: Nanotechnology; Melanoma; Cancer; Physiological metal oxides